New wars and new soldiers military ethics in the contemporary world - Tripodi, Paolo; Wolfendale, Jessica (Ashgate Publishing Company, 2011)
How, then, should military ethics approach these new forms of conflict? Modern military ethics now includes work from disciplines as diverse as philosophy, history, sociology, international relations, politics, and psychology.